Influence of Concentration Distribution on Cross Diffusion Level in Building Room - Zhehua Du (E3S Web of Conferences, 2021)
The relationship of contaminant gas concentration distribution influence on cross diffusion character and level among temperature, humidity and contaminant gas concentration was obtained according to the non-equilibrium thermodynamic theory. The cross diffusion character and level under different contaminant gas concentration distribution were discussed, combining real temperature and humidity in building room. The results show that temperature grads and vapor mass grads are less than zero when contaminant gas mass grads and additional diffusion coefficient are both positive or negative, otherwise the two grads are more than zero. And the higher the initial temperature and humidity levels, the greater the absolute values of temperature grads and vapor mass grads, with the same contaminant gas mass grads and additional diffusion coefficient. While the influence of initial temperature level is finite, and that of initial humidity level is remarkable.